Peningkatan Kapasitas Produksi dan Pemasaran melalui Integrasi Teknologi Produksi dan Digital Marketing UMKM Kerupuk Kemplang Ummi - Taufik Rahman; Dwi Agus Riyanto; Pipiet Mutiara Trisentian (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Crackers made from wheat flour and processed fish have become a popular snack among Indonesian consumers. Mrs. Ratih Wardani, owner of Ummi Kemplang Crackers MSME located on Jalan Gatot Subroto, Gang Serasan 1, Bumi Raya Village, Bumi Waras District, Bandar Lampung City, encounters significant obstacles in marketing her products. Narrow market reach hinders business expansion. MSMEs play a vital role in Indonesia's economic development by utilizing local resources. However, digital transformation has become an urgent necessity to expand market reach, accompanied by improved financial management. This community service program aims to enhance production capacity and marketing strategies. Production process modernization is expected to boost the economic welfare of business partners. Marketing improvements were achieved through developing an online sales website that reaches local, national, and international markets. The provision of mixing and cutting machines successfully increased production capacity by 30% while opening opportunities for product diversification.